CO2 sorption performance by aminosilane functionalized spheres prepared via co‐condensation and post‐synthesis methods. Issue 8 (6th April 2016) - Madden, David; Curtin, Teresa; Hanrahan, John P.; Tobin, Joseph
Abstract : Amine functionalized silica microspheres were synthesised via a modified Stöber reaction for carbon dioxide (CO2 ) adsorption. A number of adsorbents were synthesized by co‐condensation and post synthesis immobilization of amines on porous silica spheres. CO2 adsorption studies were carried out on a fixed bed gas adsorption rig with online mass spectrometry. Amine co‐condensed silica spheres were found to adsorb up to 66 mg CO2 g −1 solid in a 0.15 atm CO2 stream at 35°C. Simple post‐synthesis addition of aminopropyltriethoxysilane to amine co‐condensed silica was found to significantly increase the uptake of CO2 to 211 mg CO2 g −1 under similar conditions, with CO2 desorption commencing at temperatures as low as 60°C. The optimum temperature for adsorption was found to be 35°C. This work presents a CO2 adsorbent prepared via a simple synthesis method, with a high CO2 adsorption capacity and favorable CO2 adsorption/desorption performance under simulated flue gas conditions. © 2016 American Institute of Chemical Engineers AIChE J, 62: 2825–2832, 2016